Poder e resistências: movimentações da multidão - uma cartografia dos movimentos antiglobalização - Andreotti, Bruno Leonardo Ramos (2009)
The anti-globalization movements rose out from the political scenario around the 90 s as a way of resistance to the neoliberalism and globalization. Recognizing the Zapatista Army of National Liberation as the original inspiration, the People s Global Action (PGA) is established in 1988 for the purpose of being a global union of resistance against the global market and subsequently against the capitalism. Its majors manifestations were the Global Action Days, coordinated direct actions occurring at many locations through the planet with the intent of stop the international capitalism managers meeting, opposing to capitalism and its institutions. Among the most known are Seattle (1999) and Genoa (2001). These movements of resistance were organized by affinity groups, direct actions self managed performed. One part of the movement, searching for legitimacy, establishes a dissociation between violent direct action and non-violent, the first, illegitimate and illegal, the second, working as a mean to reach a particular revendication. From this splitting, these movements are captured in an attempt of unification with the World Social Forum, that intends to elaborate concrete projects for an alternative globalization. Its foundation is the organization of civil society towards citizen regulation of the capital, attempting political leading actions aiming to deepening citizenship and democratical participation. These leading actions were amplified and developed in the magazine Global Brasil, out from the World Social Forum. These resistances have in common a new proposal of organization: no more the hierarchy of the party, but the horizontality of the network, that allows multiple connections with plenty movements. This new organization model permits some marxits, specially Antonio Negri, perceive this new organization and resistance type in the concept of multitude, that provides an actualization of the proletariat concept and the accomplishment of a new protagonist to the class struggles engaged through history. This research achieves a cartography of these resistances, the trace of the lines molecular, molar and the line of flight that rises out from the antiglobalization movements and apprehended through the concept of multitude. By the study of these lines it was possible to settle a characterization of the resistence of the multitude as inclined to captures, encoding and overcoding, different from the resistances that work by uncoding, becomings, inventions of spaces of liberty